The Effect of Bone-Loading Exercise on Bone Mineral Density in Women Following Treatment for Breast Cancer: A Systematic Review and Meta-analysis. Issue 4 (October 2016) - Zerzan, Sarah; Smoot, Betty; Lee, Jeannette Q.; Lui, Andrew; Allen, Diane D.
Abstract : Purpose: The purpose of this systematic review and meta-analysis was to synthesize the current literature on the effects of bone-loading exercise on bone mineral density (BMD) in women after treatment of breast cancer (BC). Methods: PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Physiotherapy Evidence Database (PEDro), and Web of Science databases were searched through March 31, 2016. A combination of MeSH terms and key words was used: (physical therapy OR physiotherapy OR resistance training OR weight training OR aerobic OR exercise) AND (bone density OR osteoporosis) AND breast cancer. Search terms for PEDro were as follows: (breast cancer AND bone breast cancer) and (breast cancer AND osteoporosis). Studies included were experimental studies that compared any type of bone-loading exercise intervention with a comparison group and reported dual-energy x-ray absorptiometry for assessment of BMD of the lumbar spine and/or proximal femur (femoral neck, trochanter, and/or total hip). Between-group BMD effect sizes and 95% confidence intervals (CIs) were calculated for each study (bone-loading exercise vs usual care/non–bone-loading exercise) and pooled across studies. Risk of bias in and across studies was addressed using the PEDro scale. Results: Five randomized controlled studies were included. Pooled effect sizes were statistically significant, favoring the bone-loading exercise group for proximal femur ( d = 0.15; 95% CI, 0.03-0.28) and for lumbar spine BMD ( d = 0.14; 95% CI, 0.01-0.27). Conclusion: Results provide modest evidence that bone-loading exercise interventions have statistically and clinically significant effects on proximal femur and lumbar spine BMD in women treated for BC. Further research is warranted to determine the most effective types and intensities of exercise for improving BMD in BC survivors.